THE ANXIOUS EFFECT OF CHARACTER'S SWITCHING BODY IN WEBTOONS COMIC LOOKISM - Nurul Chusna; Amin Khudlori (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
The existence of comics cannot be underestimated because in addition to trying to show sociological and physiological conditions, comics also record psychological symptomsrevealed through the dynamics of the personality of the characters contained in the story. The personality dynamics seen through the behavior of these figures help to reveal the meaning of the story as a whole.Psychologists have categorized defense mechanisms based upon how primitive they are. The more primitive a defense mechanism, the less effective it works for a person over the longterm. However, more primitive defense mechanisms are usually very effective short-term, and hence are favored by many people and children especially (when such primitive defense mechanisms are first learned). Adults who don’t learn better ways of coping with stress or traumatic events in their lives will often resort to such primitive defense mechanisms as well.The writer uses two methods of data collection to do this research about “The Anxious Effect of Character’s Switching Body in Webtoons Comic  Lookism”. They are library research anddescryptive analysis. the anxiety that Daniel Park exhibits is the neurotic anxiety, which appears continuously for fear of danger that seems to be threatening. Daniel Park's anxiety serves as a sign that there will be danger.Keywords: Webtoons, Personality, Defense Mechanism, Switching Body and Anxiety.